Grouting of tendons in prestressed concrete (FIP guide to good practice., 1990)
Deals with the grouting of tendons inside concrete members using cement grout, and tackles the day to day matters, which produce good grouting. After a review of objectives, this guide looks at ducts, inlets and outlets, grout materials and grout properties, equipment, site preparations, the grouting operation, site control, and after-measures.